Promotion of physical activity-related health competence using digital workplace-based health promotion: protocol for a controlled before-and-after study. (27th January 2023) - Oppermann, Leonard; Dierks, Marie-Luise
Abstract : Physical activity (PA) has a high potential to prevent chronic diseases. At the same time, many people in Germany do not achieve PA recommendations due to trends such as digitalisation and the COVID-19 pandemic and, as a result, working from home. There is a need for location-independent and time-independent interventions. Based on the model of physical activity-related health competence (PAHCO), a study design was developed for a digitally conducted, controlled, before-and-after-study targeting office workers. The intervention group receives video-based instructions with exercises that can be performed directly at the desk, complemented by anatomical explanations and advice on PA based on the PAHCO model. The control group only receives the exercises. The intervention period is 5 weeks. Follow-up is conducted after 3 months. The trial shall comprise 294 participants per group whose PA is recorded via questionnaire and online PA diary. Their PAHCO and health-related quality of life are also assessed. The present study aims to increase the health-enhancing PA of office workers independent of time and location. Trial registration number is DRKS00028053.